2021
DOI: 10.1016/j.bja.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Minimal clinically important differences in randomised clinical trials on pain management after total hip and knee arthroplasty: a systematic review

Abstract: Background: Sample size determination is essential for reliable hypothesis testing in clinical trials and should rely on adequate sample size calculations with alpha, beta, variance, and an effect size being the minimal clinically important difference (MCID). This facilitates interpretation of the clinical relevance of statistically significant results. No gold standard for MCIDs exists in postoperative pain research. Methods: We searched Cochrane Central Register of Controlled Trials, MEDLINE, and Embase for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(120 citation statements)
references
References 41 publications
(43 reference statements)
3
115
2
Order By: Relevance
“…We included five RCTs and found that NMES improved postoperative pain at mid-term (1–2 months and 3–6 months) following TKA. However, the improved differences did not reach the minimal clinically important difference (MCID) in pain ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included five RCTs and found that NMES improved postoperative pain at mid-term (1–2 months and 3–6 months) following TKA. However, the improved differences did not reach the minimal clinically important difference (MCID) in pain ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we knew, this was the first systematic review and meta-analysis to comprehensively explore the effect of NMES on quadriceps muscle strength, pain, and function following TKA. However, the differences did not reach the MCID in pain (50). Given the included studies adopt different scales in many essential outcomes, the SMD was used to calculate the total effect of quadriceps muscle strength and WOMAC, which may generate issues with heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, the MD in pain scores ranged from 0.58 at 2–4 h to 1.28 at 24 h. Indeed, the difference is not large and the clinical relevance of reduced pain with ketorolac can be questionable. In a recent study, Laigaard et al [ 31 ] have shown that MCID for pain after hip/knee arthroplasty is 1.5 on VAS. Olsen et al [ 30 ] in their systematic review have suggested that MCID can range from 0.8 to 4 for acute pain and can vary with baseline pain, definitions of improved patients, and study design.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Thus, it was unclear whether absolute decrease in 24-h intravenous milligram morphine consumption in the TPVB group exceeded the recommended minimal clinically important difference in the literature, ie, an absolute reduction of 10 mg intravenous morphine. 6 …”
Section: Dear Editormentioning
confidence: 99%